2019
DOI: 10.1007/s11130-019-00723-z
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-Based Fat Mimetics Can Affect the Levels of 3-Monochloropropane-1,2-Diol Esters and Glycidyl Esters in Shortbread Biscuits

Abstract: Shortbread biscuits have become one of the most desirable snacks in all population groups but due to its high fat content it is searching for new solutions of fat reduction such as the use of carbohydrate-based fat mimetics. However, the thermal processing of food containing lipids in the presence of certain carbohydrates can contribute to the formation of toxic compounds or alter its levels. Therefore, the aim of the study was to evaluate the use of inulin and pectin gels as partial fat replacers (10–40%) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The decrease in GE content for both the coated and control samples indicated that due to the presence of an epoxide group in its structure, the unstable GE might react with other food components (Cheng et al ., 2017). Sadowska‐Rociek & Cieslik (2019) found that the GE content of biscuits decreased from 130 to 65 μg kg −1 during 2 months of storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in GE content for both the coated and control samples indicated that due to the presence of an epoxide group in its structure, the unstable GE might react with other food components (Cheng et al ., 2017). Sadowska‐Rociek & Cieslik (2019) found that the GE content of biscuits decreased from 130 to 65 μg kg −1 during 2 months of storage.…”
Section: Resultsmentioning
confidence: 99%
“…Determination of the water contentThis method was performed according to a previous study(Sadowska-Rociek & Cieslik, 2019). The weightloss method was used.…”
mentioning
confidence: 99%
“…The authors also deduced that pectin caused a lower pH in the biscuit dough and caused a certain amount of GE decaying (A. Sadowska-Rociek and Cieslik, 2019 ). Since pectin trapped the water molecules, they cannot participate in the hydrolysis reactions to form 3-MCPD esters and GE.…”
Section: Introductionmentioning
confidence: 99%
“…The method was based on a previous study 17 . The Soxhlet extraction method and weight reduction method were used.…”
Section: Product Characteristics Analysismentioning
confidence: 99%